A preliminary investigation of cognitive function in rheumatoid arthritis patients on long-term methotrexate treatment. (October 2013) - Meade, Tanya; Cumming, Steven; Hallab, Lisa; Spencer, David; Howe, Graydon; Manolios, Nicholas
Some studies suggest that cognitive function is impaired in rheumatoid arthritis patients. One possible influence may be commonly used rheumatoid arthritis treatment, methotrexate. This study examined cognitive function in long-term methotrexate users with rheumatoid arthritis and, using a 24-hour pre- and post-methotrexate dose administration, investigated whether there may be transient cognitive function changes. Rheumatoid arthritis patients ( n = 35) were assessed immediately before taking methotrexate and 24 hours later. Low and high methotrexate dose groups were then compared. Cognitive performance was unchanged across two assessment points and was within the normal range, although lower in high methotrexate dose group.